Maringa at the beginning of the 1964 civil and military dictatorship: an analysis of the indictment against the town counselor Bonifacio Martins and its developments - Dias, Reginaldo Benedito [UNESP] (Univ Estadual Londrina, 2015)
The indictment against Bonifacio Martins, a town counselor in Maringa PR Brazil, brought about by the government after the establishment of the civil and military dictatorship in 1964 is analyzed. Bonifacio Martins was persecuted for his involvement in social and trade union struggles and for his presumed connections with the Brazilian Communist Party. He had to quit the office of town counselor due to his indictment by the military. He had to move from the town for safety reasons but was judged and condemned in absentia and arrested after some time. After the re-democratization of the country, he moved a case against the Brazilian government and asked for compensations due to the wrongs endured. In 2014 he received a posthumous homage when the Municipal Counsel of Maringa symbolically restituted the office he had to quit. The article also investigates the case of four other people, with personal or political relationships with Bonifacio Martins, involved in the same juridical process. These processes contribute towards an in-depth analysis of the political struggles that preceded and succeeded the 1964 military coup and the process of Brazil's re-democratization coupled to its slow transition period.
Keywords: 1964 civil and military dictatorship; Bonifacio Martins; Maringa; political Repression; Reparations